If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = r + -65 Reorder the terms: 12 = -65 + r Solving 12 = -65 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 12 + -1r = -65 + r + -1r Combine like terms: r + -1r = 0 12 + -1r = -65 + 0 12 + -1r = -65 Add '-12' to each side of the equation. 12 + -12 + -1r = -65 + -12 Combine like terms: 12 + -12 = 0 0 + -1r = -65 + -12 -1r = -65 + -12 Combine like terms: -65 + -12 = -77 -1r = -77 Divide each side by '-1'. r = 77 Simplifying r = 77
| p=3*18+27 | | s+95=-35 | | 4n+6-2n=(n-13) | | u-20=20 | | 71=63+b | | -17=x+69 | | 89=-64+w | | y-(-3)=9 | | 15=-18+a | | 25=8*6+b | | 12=3-(-1y) | | c+31=-3 | | a-22=-1 | | p=18(-64) | | 2+3(x+6)=11-(5x+15) | | 1.8r+9=-5 | | s-44=-36 | | 4b^2w^3/3c^2k+5x^2/6b^3k^2 | | 1*y=2 | | 216-5x=31x+20 | | 18=-21+y | | 45x+78=x^2 | | c-16=-79 | | p=-5(18) | | 55=81+x | | 0=-3-(-1y) | | 4t+3=t-3 | | 0y-(-1)=1 | | p=-6(18) | | 2(4b+1)=50 | | -91=9p+8 | | 91=9j+8 |